Miljøspørsmål i fokus: forskningsskipet "Andenes" på vei mot Antarktis - Friberg, Fred (Svalbardposten, 1989)
Keywords: Dronning Maud Land; ekspedisjoner

Anomalous palaeomagnetic directions in a Mesozoic basaltic dyke; arguments for fault-induced remagnetization - Løvlie, Reidar; Mitchell, John (Physics of the earth and planetary interiors, 1989)
Anomalously steep palaeomagnetic directions from the central part of an ∼ 5 m wide basaltic dyke from Fossilryggen, East Antarctica, suggest a Recent to late Tertiary age for its remanent magnetization, in conflict with KAr isotope ages of 162 ± 4 and 217 ± 3 Ma obtained from the central and slickenside margins respectively. Three neighbouring basaltic intrusions carry stable magnetizations whose directions (mean D, 23°; mean I, −40° and pole position, 38°N, 40°E) accord with previously obtained Mesozoic results from lava flows in the Vestfjella basalt province, East Antarctica. Rock magnetic properties do not discriminate between the different dykes, and it is proposed that the anomalous directions represent spot-readings of the geomagnetic field which arise from complete remagnetization during a period of faulting in Recent to late Tertiary times.
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; geofysikk; geologi

A hundred years of Norwegian exploration of the polar regions - Orheim, Olav (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1989)
Publisher: Routledge
Keywords: Antarktis; Norge; ekspedisjoner; oppdagelsesreiser; polarområdene

Navigation to nest site in the snow petrel (Pagodroma nivea) - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (The Condor, 1988)
Publisher: American Ornithological Society
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Sydpolen 1910-1912 - Huntford, Roland; Hoff, Truls (Roald Amundsens oppdagelsesreiser i bilder, 1988)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Early geological exploration of Seymour Island, Antarctica - Zinsmeister, William J (Geology and Paleontology of Seymour Island, Antarctic Peninsula, 1988)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Seymourøya; Vestantarktis; ekspedisjoner; forskning; geologi; hvalfangere; oppdagelsesreiser

Breeding ecology of the Antarctic petrel Thalassoica Antarctica in Mühlig-Hofmannfjella, Dronning Maud Land - Fridtjof, Mehlum; Claus, Bech; Svein, Haftorn (Proceedings of the NIPR Symposium on Polar Biology, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Interrelationships between egg dimensions, pore numbers, incubation time, and adult body mass in Procellariiformes with special reference to the Antarctic petrel Thalassoica antarctica - Mehlum, Fridtjof; Rahn, Hermann; Bech, Claus; Haftorn, Svein (Polar Research, 1987)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Bryophytes of Bouvetøya - Bell, Graham B; Blom, Hans H (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Botany of two Antarctic mountain ranges: Gjelsvikfjella and Mühlig-Hofmannfjella, Dronning Maud Land. I. General ecology and development of the Antarctic cold desert cryptogam formation - Engelskjøn, Torstein (Polar Research, 1986)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; forskning; planter

General outline of the botanical investigations on Bouvetøya - Engelskjøn, Torstein (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner

Phytogeographical relations of the cryptogamic flora of Bouvetøya - Engelskjøn, Torstein; Jørgensen, Per Magnus (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; lav

A quantitative analysis of the behaviour of the Chinstrap penguin Pygoscelis antarctica and Macaroni penguin Eudyptes chrysolophus on Bouvetoya during the late incubation and early nestling periods - Haftorn, Svein (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; pingviner; zoologi

Lichens and lichen parasites from the British-Swedish-Norwegian antarctic expedition 1949-52 to Dronning Maud Land - Øvstedal, Dag Olav (Cryptogamie: bryologie, lichenologie, 1986)
Keywords: Dronning Maud Land; botanikk; ekspedisjoner; lav; parasitter; planter

Lamprospora miniatopsis Spooner, a bryophilous discomycete from Bouvetøya - Schumacher, Trond (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

New records of terrestrial arthropods from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Research, 1986)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Terrestrial arthropods of Bouvetøya - Sømme, Lauritz (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; forskning; midder; miter; virvelløse dyr

Suksess i syd: utvidet forskning i Antarktis (Forsvarets forum, 1985)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; logistikk

Botany of Gjelsvikfjella and Muhlig-Hofmannfjella, Dronning Maud Land - Engelskjøn, Torstein (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; botanikk; ekspedisjoner; planter

Oceanographic conditions on the Weddell Sea Shelf during the German Antarctic Expedition 1979/80 - Foldvik, Arne; Gammelsrød, Tor; Slotsvik, Noralf; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; hydrografi; isshelf; oseanografi

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

På ekspedisjon til Sørpolen - Moberg, John (Norsk barneblad, 1985)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; ekspedisjoner; geofysikk; glasiologi; teknologi

Terrestrial Habitats - invertebrates - Sømme, Lauritz (Antarctica, 1985)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Snorre til Sydpolen: 38 dager på isen (Status (Statoil), 1984)
Keywords: Dronning Maud Land; ekspedisjoner; geologi

Tabular icebergs in ocean waves - Kristensen, Monica; Squire, Vernon A; Moore, Stuart C (Nature, 1982)
Keywords: Antarktis; bølger; ekspedisjoner; glasiologi; havet; isbreer

Supercooling and winter survival in terrestrial arthropods - Sømme, Lauritz (Comparative Biochemistry and Physiology Part A: Physiology, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Analysis of wave measurements at Bouvetøya - Arntsen, Øivind A; Snuggerud, John (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; ekspedisjoner; forskning; oseanografi

Terrestrial vegetation of Bouvetøya : a preliminary account - Engelskjøn, Torstein (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; botanikk; ekspedisjoner; forskning

Morphology of the Weddell Sea and southwest Indian Ocean - Johnson, G Leonard; Vanney, Jean-René; Elverhøi, Anders; LaBrecque, John L (Deutsche Hydrografische Zeitschrift, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; tektonikk

First on the Antarctic Continent: being an account of the British Antarctic Expedition 1898-1900 - Borchgrevink, Carsten Egeberg (C. Hurst & Company; Australian National University Press, 1980)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; overvintring

Scott og Amundsen - Huntford, Roland; Christensen, Jan (Aschehoug, 1980)
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; dagbøker; ekspedisjoner; historie; oppdagelsesreiser; polarområdene

Terrestrial arthropods from Vestfjella, Dronning Maud Land (Acari, Collembola), with notes on their taxonomy - Sømme, Lauritz (Insect Systematics & Evolution, 1980)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi